El control interno en la razonabilidad de los inventarios de las sociedades mercantiles dentro de un periodo contable. - Ullauri Aguilar, Kevin Alexander; Calle Arellano, Dayana Belen (Machala : Universidad Técnica de Machala, 2024)
This research analyzes the role of internal control in inventory management within commercial companies, highlighting its impact on the reliability of financial information and strategic decision-making. It is emphasized that the absence of appropriate procedures, the lack of supervision, and ineffective application of technological tools can generate inconsistencies in accounting records, affecting the stability and credibility of companies. Through a mixed approach that integrates quantitative and qualitative analysis, this research identifies the primary deficiencies in inventory control. The study is grounded in a regulatory framework based on International Accounting Standard (IAS) 2 and IAS 8, which provide guidelines for the accurate valuation and presentation of inventories. Additionally, it underscores the significance of internal auditing and performance indicators as essential mechanisms for enhancing efficiency in inventory management. The findings reveal that many organizations lack well-defined internal control policies, resulting in financial risks such as economic losses and inaccuracies in financial reporting. This study highlights the imperative need to establish standardized procedures, improve personnel training, and optimize the use of management software to ensure reliable and efficient record-keeping. In conclusion, internal control plays a fundamental role in inventory management by ensuring the accuracy of financial information and promoting business sustainability. The implementation of effective control measures and regular audits contributes to risk mitigation and enhances the competitive advantage of organizations in the marketplace.
Esta investigación analiza el papel del control interno en la gestión de inventarios dentro de las sociedades mercantiles, destacando su impacto en la razonabilidad de la información financiera y en la toma de decisiones estratégicas. Se enfatiza que la ausencia de procedimientos adecuados, la falta de supervisión y la deficiente aplicación de herramientas tecnológicas pueden generar inconsistencias en los registros contables, afectando la estabilidad y credibilidad de las empresas. A través de un enfoque mixto, combinando análisis cuantitativo y cualitativo, se identifican las principales deficiencias en el control de inventarios. La investigación se apoya en un marco normativo basado en la NIC 2 y la NIC 8, las cuales establecen lineamientos para la correcta valoración y presentación de los inventarios. Se destaca la importancia de la auditoría interna y de los indicadores de desempeño para mejorar la eficiencia en la administración de los inventarios. Los resultados evidencian que muchas empresas carecen de políticas claras de control interno, lo que conlleva riesgos financieros, como pérdidas económicas y problemas en la presentación de información contable. Se resalta la necesidad de establecer procedimientos estandarizados, mejorar la capacitación del personal y optimizar el uso de software de gestión para garantizar registros confiables y eficientes. En conclusión, el control interno juega un papel fundamental en la gestión de inventarios, asegurando la precisión de la información financiera y la sostenibilidad empresarial. Implementar controles efectivos y auditorías regulares permite reducir riesgos y mejorar la competitividad de las organizaciones en el mercado.
Keywords: CONTROL INTERNO; AUDITORIA; INVENTARIOS; NIC 2